The Environmental Caring Character through Activities to Maintain School Cleanliness - Muklis Riyanto; Tri Juli Hajani; Sri Eva Mislawaty; Zuhri Zuhri; Agung Subakti; Agussalim Agussalim; Desi Tri Anggereni; Nik Haryanti; Elce Purwandari (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The character of caring for the environment is a character that must be implemented in schools at every level of education. This study aims to determine the character of caring for the environment through activities to maintain school cleanliness at Madrasah Ibtidaiyah Nur Riska, Lubuklinggau City. The research subjects were 16 students at Nur Riska Madrasah Ibtidaiyah Nur Riska, Lubuklinggau City. The method used in this research is quantitative in the form of a survey. Data collection techniques through questionnaires given to respondents. Data analysis techniques were performed using descriptive statistics. The results of the study revealed that students are diligent in maintaining the cleanliness of the school environment around the classroom, canteen, and toilets. Only a few students have not maintained the cleanliness of the school environment properly. Many students can maintain the cleanliness of the environment around the school well, they don't litter, and the class conditions are quite clean, beautiful, and comfortable, so students also feel comfortable doing the learning process and concentrate more when the classroom conditions are clean. The research contribution can provide understanding for other schools who want to know the character of caring for the environment through activities to maintain school cleanliness.